FORMULATION DEVELOPMENT AND EVALUATION OF ALLOPURINOL SOLID DISPERSIONS BY SOLVENT EVAPORATION TECHNIQUE - Prasad, Ramshetti Rajendra; Kumar, Jadi Rajendra; Vasudha, Bakshi; Kumar, Chettupalli Ananda (International Journal of Applied Pharmaceutics, 2018)
Objective: The main objective of the research work is to develop and characterize allopurinol (ALPN) solid dispersions with different polymers to enhance solubility, enrich dissolution profile and improve patient compliance. Methods: ALPN solid dispersions were prepared by solvent evaporation technique using various grades of polyethelene glycol (PEG) such as PEG 4000 and PEG 6000 with different ratios like 1:0.5, 1:1, 1:1.5 and 1:2 and after formation of solid dispersions all physicochemical properties were examined. Results: All the formulations were found within the permissible pharmacopoeial limits for various physicochemical parameters. The pre-formulation studies, like Fourier, transform infrared spectroscopy (FTIR) showed the absence of drug-excipient interactions. The solubility and dissolution profiles of the sample were increased with increasing the concentration of ALPN solid dispersions. Solvent evaporation was proved to be a successful technique for the development of stable solid dispersion of ALPN. The dissolution amount percentage of ALPN formulations was found between 39.58±2.5 to 94.95±1.8 % within 60 min. Conclusion: Hence, from the all evaluation studies, it was evident that F1 formulation was the better formulation. F1 formulation (ALPN: PEG 4000 in the ratio of 1:0.5), 94.95±1.8 % drug released within 50 min.